Functionally distinct contributions of the anterior and posterior putamen during sublexical and lexical reading - Oberhuber, Marion; Parker Jones, ‘Ōiwi; Hope, Thomas M H; Prejawa, Susan; Seghier, Mohamed L.; Green, David W.; Price, Cathy J. (Frontiers in Human Neuroscience, 2013)
Previous studies have investigated orthographic-to-phonological mapping during reading by comparing brain activation for (1) reading words to object naming, or (2) reading pseudowords (e.g. “phume”) to words (e.g. “plume”). Here we combined both approaches to provide new insights into the underlying neural mechanisms. In fMRI data from 25 healthy adult readers, we first identified activation that was greater for reading words and pseudowords relative to picture and color naming. The most significant effect was observed in the left putamen, extending to both anterior and posterior borders. Second, consistent with previous studies, we show that both the anterior and posterior putamen are involved in articulating speech with greater activation during our overt speech production tasks (reading, repetition, object naming and color naming) than silent one-back-matching on the same stimuli. Third, we compared putamen activation for words versus pseudowords during overt reading and auditory repetition. This revealed that the anterior putamen was most activated by reading pseudowords, whereas the posterior putamen was most activated by words irrespective of whether the task was reading words or auditory word repetition. The pseudoword effect in the anterior putamen is consistent with prior studies that associated this region with the initiation of novel sequences of movements. In contrast, the heightened word response in the posterior putamen is consistent with other studies that associated this region with “memory guided movement”. Our results illustrate how the functional dissociation between the anterior and posterior putamen supports sublexical and lexical processing during reading.